Association between poverty and children's working memory abilities in developing countries: a systematic review and meta-analysis - Nugroho, Hari Wahyu; Salimo, Harsono; Hartono, Hartono; Hakim, Moh. Abdul; Probandari, Ari (Frontiers in Nutrition, 2023)
Working memory is critical in cognitive skills, especially among children. Children’s ability to count and complete cognitive tasks is strongly associated with working memory abilities. Recent studies indicated that in addition to health factors, socioeconomic status also has a significant impact on children’s working memory capacity. Despite these, evidence on the effects of socioeconomic status on working memory from developing countries yielded a somewhat puzzling picture. This systematic review and meta-analysis provide a comprehensive summary of the recent evidence concerning the socioeconomic status determinants of children’s working memory in developing countries. We searched via Cochrane library, ScienceDirect, Scopus, PubMed, and ProQuest. The initial search terms were ['socioeconomic', 'socio-economic', 'socioeconomic status', 'socio-economic status', 'income', 'poverty', 'disadvantaged' 'disparity'] AND ['working memory', short term memory', short-term memory', 'cognitive', 'achievement', 'performance'] AND [‘child*’, ‘school child*]. Odds ratio (for categorical outcome data) or standardized mean differences (for continuous data) and their 95% confidence intervals were calculated from the data generated. This meta-analysis included five studies from 4 developing countries with a total of 4551 subjects. Poverty was associated with a lower working memory score (OR: 3.12; 95% CI: 2.66, 3.65; p <0.001). Another finding from 2 studies in this meta-analysis was that low mother education was associated with a lower score of working memory (OR: 3.26, 95% CI: 2.86, 3.71; p <0.001). Poverty and low level of mothers’ education were significant risk factors for lowering working memory among children in developing countries.